Treatment of Early Onset Schizophrenia: Recent Trends, Challenges and Future Considerations - Vyas, Nora S.; Gogtay, Nitin (Frontiers in Psychiatry, 2012)
Early onset schizophrenia (onset before adulthood) is a rare, severe and chronic form of schizophrenia. Antipsychotic treatment remains the mainstay of treatment although current medications provide suboptimal response at best. Early detection, identification of relevant biomarkers, coupled with advancing knowledge of the neurochemical and neuroanatomic pathways may help design informed prevention and/or treatment strategies.